The parallelization of the Keller box method on heterogeneous cluster of workstations - Hamzah, Norhafizah (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2008)
High performance computing is the branch of parallel computing dealing with very large problems and large parallel computers that can solve those problems in a reasonable amount of time. This paper will describe the parallelization of the Keller-box method using the high performance computing on heterogeneous cluster of workstations. The problem statement is based on the equation of boundary-layer flow due to a moving flat plate. The objective is to develop the parallel algorithm of the Keller-box method in purpose to solve a large size of matrix. The parallelization is based on the domain decomposition, where the upper and lower matrices will be splitting into a number of blocks, which then will be compute concurrently on the parallel computers. The experiment was run using 200, 2000, and 20000 size of matrices and using 10 number of processors. The comparison was made from the results obtained from that various size of matrices by doing the analysis based on the performance measurement in terms of time execution, speedup, and effectiveness.